The Parenting for Lifelong Health Caring Families programme with parents of young children in North Wales: a qualitative study of participant feedback - Carly DeLuca; Jen Lunt; Judy Hutchings (Frontiers in Developmental Psychology, 2026)
The Parenting for Lifelong Health for Young Children (PLH-YC) programme was originally developed as a low-cost, evidence-based parenting intervention for families in low- and middle- income countries. However, in response to reductions in early intervention service funding in the UK, the programme was piloted in two socioeconomically disadvantaged communities in North Wales. Building on quantitative feasibility findings that demonstrated high retention, strong participant satisfaction, and significant improvements in parenting practices and parental wellbeing, this qualitative study explored the lived experiences of ten parents who participated in the programme. Semi-structured interviews were analyzed using Braun and Clarke's thematic analysis approach. Three major themes emerged: learning to parent differently, creating a circle of support, and wanting more time. Parents reported increased confidence, improved emotional regulation, and enhanced relationships with their children. These findings reinforce the feasibility and acceptability of the PLH-YC programme in a UK context and align with the quantitative evidence of its positive impact internationally. Together, the UK studies indicate that PLH-YC is a promising, low-cost intervention that with further evidence has the potential to contribute to services to strengthen parenting practices in the UK for parents of children at risk of poor outcomes.